4CPS-243 Healthcare associated Clostridioides difficile infection in surgical and medical patients. (14th March 2021) - Peric, A; Suljagic, V; Milenkovic, B; Vezmar Kovacevic, S
Abstract : Background and importance: Clostridioides difficile ( C difficile ) infection (CDI) is one of the most common healthcare associated (HA) infections in contemporary medicine. The risk factors (RFs) for HA CDI in medical and surgical patients are poorly investigated in countries with a limited resource healthcare system. Aim and objectives: To investigate differences in patient characteristics and RFs associated with HA CDI in surgical and medical patients. Material and methods: A prospective cohort study was conducted including adult patients diagnosed with an initial episode of HA CDI from 2011 to 2017 in a 1200 bed teaching hospital. Patients hospitalised for any non-surgical illness, who developed initial HA CDI, were assigned to the medical group, whereas those who developed initial HA CDI after surgical procedures were in the surgical group. Data on the use of proton pump inhibitors (PPIs), chemotherapy and antibiotic usage were gathered by hospital pharmacists. Results: From 553 patients diagnosed with HA CDI, 268 (48.5%) and 285 (51.5%) were surgical and medical patients, respectively. Medical patients were significantly older than surgical patients (68.59±15.46 vs 64.91±14.86 years, p=0.005), and were treated significantly more frequently with PPIs (38.9% vs 19%, p<0.001), fluoroquinolones (28.6% vs 9.9%, p<0.001) and chemotherapy (12.6% vs 1.9%, p<0.001). Admission to the intensive care unit (ICU) was significantly more frequent in surgical patients (35.4% vs 10.9%, p<0.001) as well as use of second and third generation cephalosporins (30.0% vs 17.6%, p=0.001; 64.6% vs 53.1%, p=0.007, respectively). Conclusion and relevance: Age ≥65 years, use of PPIs, chemotherapy and fluoroquinolones were positively associated with the medical group and were significant predictors of CDI, whereas admission to the ICU and the use of second and third generation cephalosporins were positively associated with being in the surgical group and were significant predictors of CDI. We conclude that medical patients were more endangered with HA CDI than surgical patients. References and/or acknowledgements: Perić A, Dragojević- Simić V, Milenković B, et al . Antibiotic consumption and healthcare-associated infections in a tertiary hospital in Belgrade, Serbia from 2011 to 2016. J Infect Dev Ctries 2018;12 :855–863. Šuljagić V, Miljković I, Starčević S, et al . Risk factors for Clostridioides difficile infection in surgical patients hospitalised in a tertiary hospital in Belgrade, Serbia: case-control study. Antimicrob Resist Infect Control 2017;6 :31. Conflict of interest: No conflict of interest